Effect of trisodium citrate on morphological, structural, and optical properties of fluorine-doped ZnO structures. Issue 10 (15th May 2022) - Muhammad, A.; Hassan, Z.; Mohammad, Sabah M.; Rajamanickam, Suvindraj; Shitu, Ibrahim Garba
Abstract: In this work, we present the effect of trisodium citrate (TSC) addition via a hydrothermal method on the morphological, compositional, structural, and optical changes of fluorine-doped zinc oxide (FZO) on silicon substrates. Field emission scanning electron microscopy revealed vertically aligned nanorods for FZO and pebble and block-like microstructures of different sizes upon TSC addition. X-ray diffraction analysis revealed a hexagonal structure for all the samples. Upon addition of TSC, the sample growth along the c-axis was inhibited strongly and the growth along the a-axis was developed. The crystallite size increased from 28.73 nm to 30.38 nm upon addition of TSC. The oxygen deficiency and, the presence of zinc, oxygen, fluorine, and sodium in the studied samples were confirmed by energy-dispersive X-ray analysis and X-ray photoelectron spectroscopy (XPS). Ultraviolet (UV)-visible analysis revealed the optical energy band gap increment from 3.204 eV to 3.241 eV with TSC addition. Photoluminescence (PL) analysis revealed a significant improvement in the intensity ratio of the near band emission to deep level emission from 5.44 to 12.59 upon TSC addition, indicating crystal quality improvement. Both UV–visible and PL analyses showed that the studied samples were blue-shifted upon TSC addition. The different morphologies with promising properties could be employed in different applications, eliminating the complexity and reducing cost in the fabrication of hybrid structures, and nano/microcomposites.